Description of two new species of Lithoxus (Hypostominae: Loricariidae) from rio Jari and rio Amapa basins, Brazilian Guiana Shield - Silva, Gabriel S. C. [UNESP]; Covain, Raphael; Oliveira, Claudio [UNESP]; Roxo, Fabio F. [UNESP] (Magnolia Press, 2017)
Two new species of Lithoxus, a genus diagnosed by possessing a dorsoventrally depressed body, a large round oral disk, and small tooth cusps with few teeth, are described from two drainages of the Guiana Shield: Lithoxus jariensis from the rio Jari basin and L. raso from the rio Raso, rio Amapa basin. The new species, L. jariensis, is distinguished from congeners by having an adipose fin, by the number of branched anal-fin and caudal-fin rays, by color pattern of the body, number of teeth, adipose-fin length, dorsal adipose-caudal distance, caudal peduncle depth, cleithral width, and dorsal-anal distance. Lithoxus raso can be diagnosed from congeners by coloration pattern, by having an adipose fin, by the number of branched anal-fin rays, number of teeth, adipose-fin length, dorsal adipose-caudal distance, caudal peduncle depth, and cleithral width. Greater genetic divergence in mitochondrial cytochrome oxidase subunit I (COI) confirms L. jariensis and L. raso as two new species.
Keywords: COI gene; DNA barcode; Guiana Shield; Amapa State; Neotropical fish